Agencies of transition: why German coal workers are not accepting an energy transition despite social provisions - Nicole Kleinheisterkamp-González (Environmental Research: Energy)
This study explores the complexities of Germany’s energy transition, focusing on coal workers and their unions. Drawing from labor geography, the article examines how workers navigate the challenges of the coal phase-out. Despite strong union representation, co-determination rights, and negotiated economic provisions, coal workers express significant concerns about industry restructuring. These concerns are categorized into two main areas: personal futures and the broader societal impacts of the transition. Workers fear deindustrialization, social decline, and an exacerbation of austerity effects, leading to a prevalent rejection of Germany’s green transition. Additionally, a rightward political shift has been observed, which is linked to fears of social decline. This study highlights the importance of considering these factors in policy discussions, advocating for a just transition that addresses both the immediate material anxieties and the broader societal impacts experienced by workers.